Detection of AMR in ESBL-Producing E. coli Isolated from Indigenous, Layers and Broiler Chickens in Morogoro Municipal Markets, Tanzania - Brenda Peter; Alexander Mzula; Abubakar Hoza (Journal of Applied Veterinary Science And Technology, 2026)
Background: Antimicrobial resistance is a global public health threat, undermining the prevention and treatment of infectious diseases in humans and animals. Purpose:  Investigated the antimicrobial resistance profiles and molecular characteristics of ESBL-producing E. coli from live-bird markets to evaluate their potential as sources of contamination and transmission of resistant bacteria. Method: In this cross-sectional study, 300 cloacal swabs from indigenous, broiler, and layer chickens across three markets (Bigwa, Kingalu, Mawenzi) were cultured for E. coli using standard microbiological and biochemical methods. Antimicrobial susceptibility was assessed by Kirby-Bauer disk diffusion following CLSI guidelines. ESBL production was confirmed phenotypically by the Combined Disk Test, and ESBL genes (blaTEM, blaCTX-M, blaSHV) were detected by PCR. Data were analyzed using Microsoft Excel, Epi Info™ 7, and Chi-square tests. Results: Of 300 samples, E. coli was isolated in 98.3% (n=294), with 78.9% (n=263) showing multidrug resistance (MDR). MDR prevalence varied significantly by poultry type (p<0.0001): broilers (100%), layers (85%), and indigenous chickens (79%). High resistance was observed to ciprofloxacin (75.8% broilers, 63% layers, 24% indigenous) and ampicillin (100% broilers, 43% layers, 72% indigenous). Among ESBL genes, only blaTEM was detected (2.7%, n=8), while blaCTX-M and blaSHV were absent.  Conclusion: These findings underscore the role of poultry and live-bird markets in disseminating antimicrobial-resistant bacteria with potential human transmission. Strengthened surveillance, public awareness, prudent antibiotic use, and enhanced biosecurity including vaccination and improved hygiene are essential to mitigate AMR, prevent disease, and reduce reliance on antimicrobials.